Antihyperlipidemic Activity of Tamarind (Tamarindus indica) Extract on the Lipid Profile of Albino Rats - Christijanti, Wulan; Susanti, R.; Rakainsa, Senda Kartika; Widyaningrum, Kartika; Mohamed, Mohd Salim Bin (Biosaintifika: Journal of Biology & Biology Education, 2024)
Tamarind are widely used as antioxidants, anti-diabetes, anti-hyperlipidemia, and anti-cholesterolemia. The aim of this research is to analyze the anti-hyperlipidemic activity of extracts of tamarind fruit pulp, seeds and leaves on the lipid profile of rats. Experimental research was designed with 20 male rats divided   Control (C), Tamarind leaves (TL), Tamarind fruit pulp (TF), and Tamarind seeds (TS) extracts, each 500 mg/kg of body weight. All of the groups were given standard feed and induced with lard at 3 ml/rat/day for 14 days. On day 15, the rats were continued to be induced with lard and were given extracts according to each group for 2 weeks. The data obtained such as rats’ body weight, level of cholesterol, HDL (high-density lipoprotein), LDL (low-density lipoprotein), triglycerides (TG) and Malondialdehyde (MDA)  were analyzed using anova (P<0.05) and the Duncan Multiple Range Test (DMRT). The results showed that each extract had a significant effect on cholesterol, HDL and MDA levels but not on body weight, LDL and triglycerides. Levels of MDA in the group with the extract were significantly lower than the control. Tamarind pulp, seeds and leaf extracts show antihyperlipidemic activity by reducing cholesterol and HDL levels. This can be the basis for using parts of the tamarind plant as a supplement for the community to maintain fat levels.